2019
DOI: 10.1093/mnras/stz2073
|View full text |Cite
|
Sign up to set email alerts
|

Two families of elliptical plasma lenses

Abstract: Plasma lensing is the refraction of low-frequency electromagnetic rays due to free electrons in the interstellar medium. Although the phenomenon has a distinct similarity to gravitational lensing, particularly in its mathematical description, plasma lensing introduces other additional features, such as wavelength dependence, radial rather than tangential image distortions, and strong demagnification of background sources. Axisymmetrical models of plasma lenses have been well-studied in the literature, but dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…The electron density distribution on the lens plane will influence the deflection angle to a great extent and different lens models have been developed. The most commonlyadopted model is one-dimension Gaussian lens [50,52] and more complicated light curves can be realized if other lens models are assumed [53,54].…”
Section: Plasma Lensingmentioning
confidence: 99%
“…The electron density distribution on the lens plane will influence the deflection angle to a great extent and different lens models have been developed. The most commonlyadopted model is one-dimension Gaussian lens [50,52] and more complicated light curves can be realized if other lens models are assumed [53,54].…”
Section: Plasma Lensingmentioning
confidence: 99%
“…Substituting p 2 ϕ from ( 31) into (33), we find that the equation for the radius of a circular light orbit can be compactified to the following simple form:…”
Section: Circular Light Orbitsmentioning
confidence: 99%
“…In a recent paper [30], we have investigated gravitational microlensing in the presence of plasma ('hill-hole' effect). For some other recent studies see [31][32][33][34][35][36][37][38]. Recent review of plasma effects in gravitational lensing can be found in [39].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the converging achromatic behaviour of the vacuum gravitational lenses, the frequency-dependent lensing occurs from the refraction of electromagnetic rays by the plasma along an observer's line of sight and has the diverging character for spherically symmetric distributions with falling density. Such plasma lensing has been recently studied numerically by methods of gravitational lens formalism in series of works of Er & Rogers (2018); Rogers & Er (2019); Er & Rogers (2019), see also Clegg et al (1998). Note that in studies of interstellar scintillation the plasma column density is used instead of the volume density, see Rickett (1977).…”
Section: Lens Equation In Presence Of Gravity and Plasmamentioning
confidence: 99%
“…For the wave effects in presence of Solar gravity and Solar corona, see Turyshev & Toth (2019a,b). For some recent studies see Schulze-Koops, Perlick & Schwarz (2017); Crisnejo & Gallo (2018); Crisnejo, Gallo & Rogers (2019); Er & Rogers (2018); Rogers & Er (2019); Er & Rogers (2019) ;Javed, Abbas & Övgün (2019); Sárený and Balek (2019); Crisnejo, Gallo & Jusufi (2019). Recent review of plasma effects in gravitational lensing was made by Bisnovatyi-Kogan & Tsupko (2017).…”
Section: Gravitational Lensing In Plasma: State Of Researchmentioning
confidence: 99%